A case study of online family therapy: How do clients’ expectations, therapeutic alliance, and therapeutic change interact? - Brasil, Diana Celina Pacheco (2021)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação